1996
DOI: 10.2337/diacare.19.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Bovine Serum Albumin in Brazilian Children and Young Adults With IDDM

Abstract: Our results confirm that the prevalence of anti-BSA antibodies is higher in IDDM subjects than in control subjects, even after 1 year of diabetes. However, a large overlap of antibody titers is observed in patients and control subjects, suggesting that anti-BSA antibodies are neither sensitive nor specific markers of IDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
4

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
1
10
0
4
Order By: Relevance
“…Dietary intervention trials have been planned for infants with an increased genetic risk of IDDM in order to explore the effect of avoidance of dietary cow©s milk in preventing IDDM [24]. In our comparison of age-, sex-, and HLA-DQB1-matched children with IDDM and siblings, higher levels of antibodies to cow©s milk protein antigens were found in the former.…”
Section: Discussionmentioning
confidence: 68%
“…Dietary intervention trials have been planned for infants with an increased genetic risk of IDDM in order to explore the effect of avoidance of dietary cow©s milk in preventing IDDM [24]. In our comparison of age-, sex-, and HLA-DQB1-matched children with IDDM and siblings, higher levels of antibodies to cow©s milk protein antigens were found in the former.…”
Section: Discussionmentioning
confidence: 68%
“…This could also provide an explanation for the high background and the flat profile of the serum dilution curves in some of these studies. Indeed, several publications have shown that BSA-reactive IgG Abs are present in various amounts in 20 -100% of sera from different age groups (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Much attention has been given to early infant diet [5,6], and in particular to a possible role of cow's milk [7], on the basis of studies performed in animal models that show modification of diet may influence diabetes onset [8][9][10], and of reports of increased risk of diabetes associated with reduced breast feeding time [11,12]. Moreover, the finding of specific milk proteins as targets of humoral and cell-mediated immunity to cow's milk in patients with type 1 diabetes [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] has elaborated several theories of autoimmunity induced through molecular mimicry. Although reports in favour of this hypothesis are numerous, other studies have failed to confirm the original findings [15,25,26,[28][29][30][31][32] and it still remains controversial as to whether cow's milk is involved in the autoimmunity leading to diabetes.…”
Section: Introductionmentioning
confidence: 99%